PASTORAL CARE TO THE PROSTITUTES IN JAKARTA: POSTMODERN APPROACH - Watopa, James J (Klabat Theological Review, 2022)
Prostitution is a classic social issue from ancient times until today that cannot be denied. From remote villages to megapolitan cities in every country. Some are legalized but some are prohibited. Various parties are trying to prevent and even eradicate it, but face obstacles that are difficult to resolve. For that, the church cannot turn a blind eye. There is a need for pastoral care for this issue which has disturbed the social fabric. The pastor's rarities in question include: (1) building a relationship, (2) establishing excellent and transparent communications, (3) biblical reflexivity, (4) systemic assessment, and lastly (5) planning to care. Thus, all stakeholders, not only the government, or foundations are concerned with this issue, but the church needs to make a concrete contribution to this problem. Because Jesus interacted with the prostitutes and then changed their life.  They are also, the group of people that need to be saved. Keywords :  Pastoral care, Prostitute, trafficking, transparent communications, care, building relationship, postmodernism, saved.   Bibliography Adams, Edward & Horrell, G. David (2004). Christianity at Corinth:  The Quest for the Pauline  church. Louisville, KY: Westminster John Knox Press.   Ammerman, Nancy T (1999).  Growing up Postmodern:  Imitating Christ in the age of  "Whatever." Princeton:  Institute for Youth Ministry Princeton Theological Seminary.  Bauckhan, Richard (2002).  Gospel Women:  Studies of the named women in the gospels.  Grand Rapids, Michigan:  Eerdmans Pub. Bauckhan, Richard (2003).  Bible and Mission:  Christian witness in a Postmodern World .  Grand Rapids, MI:  Baker.  Brake, Geraldine (1993). "Panama" in the Pastoral counseling in a global church . Maryknoll, NY: Orbis Books. Betan, Logo, & Dion (2020).  HIV Prevention Behaviour (condom use) among commercial sex workers based on health belief model.  Nursing update Journal ilmiah ilmu keperawatan.   Retrieved from https://sikes-nhm . E-journal.id/NU/index Blair, Allen J. (1994).  Living Victoriously:  When winning it All isn't Enough ".  Kregel Pub. Cartwright, Mark, 2009. Corinth. Retrieved from worldhitory.org/Corinth/. Collins, John J. (2005).  The Bible after Babel:  historical criticism in a postmodern age.  Grand Rapids, Michigan:  Eerdmans Cox, Harvey. (1966).  The secular city:  Secularization and urbanization in theological  Perspective.   NY: The Macmillan Company Diogenes, Allen (1989).  Christian belief in a postmodern world:  the full wealth of conviction .  Louisville:  KY:  Westminster. Doehring, Carrie. (2015).   The practice of pastoral care: a postmodern approach . Kentucky: WJK press.  Francis, Leslie J., Peter Kaldor, Mandy Robbins, and Keith Castle (2005). "Happy but exhausted?  Work-related Psychological health among clergy."  Pastoral Sciences/Sciences pastorales 24 (2)., p 101-120 Garland, D. E. (2003). 1 Corinthians (p. 220). Grand Rapids, Mich.: Baker Academic. Graham, Larry Kent (1992).  Care of persons, care of World: a psychosystems approach to pastoral care and counseling .  Nashville, TN: Abingdon.  Hiebert, Paul G. (2009). The Gospel in human contexts:  anthropological explorations for contemporary missions.   Grand Rapids, Mich:  Baker Academic.  Khairani (2019). InfoDATIN Pusat data dan Informasi kementerian Kesehatan Republik  Indonesia (Data Information Center of Ministry of Health of the Republic of Indonesia) ISSN 2442-7659. Kim, Enoch Jinsik (2017).  Mission strategy in the city .  Eugene, Oregon:  Pickwick Publications Lurie, M.N et all. (2003 ).  The impact of Migration on HIV-1 Transmission in Sout Africa:  A  study of Migrant and Non-Migrant Men and Their Partners .  Sex Transmision, Dis. 30 p (149-156).  https://csde.washington.edu/downloads/Lurie_Migration_Impact_2003.pdf MacArthur, J. (1996).  1 Corinthians (p. 146).  Chicago:  Moody Press. May, A.S. (2004).  The body for the Lord:  sex and identity in 1 Corinthians 5-7 (Vol. 278, p. 94). New York:  T & T Clark International. Patton, John (1983).  Pastoral counseling:  A ministry of the church.   Nashville:  Abingdon Press. Rokhmah, Dewi (2014).  Implikasi mobilitas penduduk dan gaya hidup seksual terhadap penularan HIV/AIDS. Retrieved from https://journal.unnes.ac.id/nju/index.php/kemas/article/view/2847 Vol 9 , No 2. Rynkiewich, Michael A. (2011).  Soul, self, and society:  A postmodern Anthropology for  Mission in a pastcolonial world .  Eugene, Oregon:  Cascade Books.  Schulze, E., Canto, Mason, & Skalin, M. (2014).  Sexual exploitation and prostitution and its  Impact on gender equality . European Parliament: Directorate-General for Internal Policies.  Soards, M.L. (2011).  1 Corinthians (p. 128).  Grand Rapids, MI:  Baker Books. Suryadinata, Arifin, & Ananta (2003).  Indonesia's Population:  Ethnicity and religion in a  changing political landscape .  Singapore:  Institute of Southeast Asian Studies.  Suyanto, Bagong (2013).  “Child Trafficking and Industry sex global.” Global & Strategy , Th.7, No.1 January-June, 2013. p. 139-154 Turner, Cambon, Greenway, Delahunty, Miller (2000). Indonesia.   Hawthorn, Victoria:  Lonely Planet Publications.